PERANCANGAN SISTEM INFORMASI PERSEDIAAN OBAT PADA TOKO OBAT ANUGERAH JAMINPA - Uliana Tetty Simatupang; Emma R. Simarmata; Gortap Lumbantoruan (Universitas Methodist Indonesia, 2021)
Medicine stores are services for products and services related to buyer satisfaction. Recording data that still uses books causes data recording to be less accurate. In addition, the problem that often occurs in a medicine store is that there is expired medicine that is not known quickly because there is no notification, and if you want to find out the existing stock you must look for one by one on the medicine stock card. The medicine inventory information system at Anugerah Jaminpa medicine store is needed as a means of containing medicine data information, stock data information, employee data information, supplier data information, sales data information, purchase data information and reports.